An investigation to identify the performance of cascade refrigeration system by adopting high-temperature circuit refrigerant R1233zd(E) over R161. (February 2023) - Patel, Vivek K.; Raja, Bansi D.; Prajapati, Parth; Parmar, Laxmikant; Jouhara, Hussam
Highlights: Multi-objective optimization of cascade refrigeration cycle. The refrigerant R1233zd(E) is investigated for the possible substitution of refrigerant R161. Investigation of the effect of operating parameters on the system performance. Investigation of the sensitivity of design variables on the thermo-economic performance. The R1233zd(E) based CRS operates with a lower total cost rate as compared to the R161. Abstract: In this work, the refrigerant R1233zd(E) (A1 ASHRAE safety code) is investigated for the possible substitution of refrigerant R161 (A2 ASHRAE safety code) in a cascade refrigeration system. The high-temperature circuit refrigerant R1233zd(E) is evaluated with the low-temperature circuit refrigerants R41 and R170 for thermo-economic consideration. A comparative analysis of the refrigerant combination R41-R1233zd(E) and R170-R1233zd(E) presents exergy efficiency and total plant cost as evaluation criteria. Pareto solutions are obtained for the thermo-economic objectives for each pair of refrigerants. A decision-making method is adopted to identify the best result from the Pareto solutions obtained. The effects of operating variables such as evaporator temperature, condenser temperature, LTC condensing temperature, and temperature difference of cascade condenser are evaluated. The sensitivity of the operating variables on thermo-economic objectives is also evaluated. The comparative results reveal that for the same total cost rate of the system (68, 615 /year), the exergy efficiencies of the CRS are 63.08% (R170-R161), 64.04% (R41-R161), 64.93% (R170-R1233zd(E)), and 65.81% (R41-R1233zd(E)). Also, the R1233zd(E) based CRS operates with a lower total cost rate than the R161-based system.